Radioluminescence degradation of scintillators on a basis of polystyrene and poly-2,4-dimethylstyrene, the ways of their radiating stability increasing - Voronkina, N.I.; Senchyshyn, V.G.; Milinchuk, V.K.; Sheluhov, I.P. (Вопросы атомной науки и техники, 2006)
Spectra of radioluminescence of plastic scintillators on a basis of polystyrene and poly-2,4-dimethylstyrene under
an influence of γ-radiation are obtained. It is shown that the most effective quenchers are macroradicals, on
which a transmission of excitation energy from “initial” luminescent additives occurs. The ways to increase PS radiating
stability are proposed. Получены спектры радиолюминесценции пластмассовых сцинтилляторов на основе полистирола и поли-2,4-диметилстирола при воздействии на них γ-излучения. Показано, что наиболее эффективными тушителями являются макрорадикалы, на которые происходит перенос энергии возбуждения с первичной люминесцирующей добавки. Предложены способы повышения радиационной стойкости ПС. Одержано спектри радіолюмінесценції пластмасових сцинтиляторів на основі полістиролу та полі-2,4-
диметилстиролу під дією γ-випромінювання. Показано, що найбільш ефективними гасниками є
макрорадикали, на які відбувається перенос енергії збудження з первинної люмінесціючої домішки.
Запропоновано способи підвищення радіаційної стійкості ПС.